2015
DOI: 10.1007/s40899-015-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects and urban impacts on aquatic macroinvertebrates in a stream of central Brazilian Cerrado

Abstract: The urban effects on macroinvertebrate trophic structure were evaluated in a stream located in central Brazilian Cerrado. Samplings were evaluated from May/ 2004 to March/2005 in the upper, middle and lower sections. Characterization of ecological conditions and habitat diversity indicated headwater as ''natural'' site, up and downstream the urban region were ''altered'' ones, and the sites located nearest to urban area were considered ''impacted''. A well oxygenated and transparent water, acid pH, low electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…Therefore, one of the ways in which urbanization facilitates guppy success is by increasing the biomass and consumption of chironomids which are highly nutritious. Such mechanism is likely to be common because chironomids are often found in large densities in aquatic urban systems worldwide and guppies, as well as other urban dwellers, have been shown to take advantage of this food resource (Kelly, Cuevas, & Ramírez, 2019; Moreyra & Padovesi‐Fonseca, 2015; Naidoo, Vosloo, & Schoeman, 2013; Sterling, Rosemond, & Wenger, 2016). Urbanization is expected to increase food availability in both aquatic and terrestrial systems (El‐Sabaawi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the ways in which urbanization facilitates guppy success is by increasing the biomass and consumption of chironomids which are highly nutritious. Such mechanism is likely to be common because chironomids are often found in large densities in aquatic urban systems worldwide and guppies, as well as other urban dwellers, have been shown to take advantage of this food resource (Kelly, Cuevas, & Ramírez, 2019; Moreyra & Padovesi‐Fonseca, 2015; Naidoo, Vosloo, & Schoeman, 2013; Sterling, Rosemond, & Wenger, 2016). Urbanization is expected to increase food availability in both aquatic and terrestrial systems (El‐Sabaawi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Táxons de macroinvertebrados presentes na nascente e trecho médio do igarapé Urumari já não são mais encontrados no trecho foz (SALCEDO, 2006;MOREYRA;PADOVESI-FONSECA, 2015), tendo assim um maior nível de contaminação no igarapé na parte mais urbanizada (PIMENTEL et al, 2019), indicando também, que não há até o momento um plano de recuperação do igarapé diante das diversas formas de impactos ambientais (PIMENTEL; MELO, 2014), onde o poder público e os diversos segmentos da sociedade civil organizada, devem estar imbuídos de traçar um planejamento de ações mitigadoras, para a recuperação do Igarapé do Urumari, visando também recuperar outros mananciais que estão sendo impactados no município de Santarém (PIMENTEL et al, 2019).…”
Section: Discussionunclassified
“…In general, there are a small number of studies related to the impact of urbanization on macroinvertebrates in aquatic ecosystems (Gal et al 2019). Our study considers the impact of urbanization on macroinvertebrate communities both in lotic and lentic habitats and characteristics of the realized ecological niche for typical urban/rural species, mitigating the evident lack of similar papers (Moreyra and Padovesi-Fonseca 2015). Numerous studies have shown that environmental factors in the catchment area (e.g.…”
Section: Introductionmentioning
confidence: 99%